ETV5 regulates ductal morphogenesis with Sox9 and is critical for regeneration from pancreatitis. Issue 6 (19th April 2018) - Das, Koushik K.; Heeg, Steffen; Pitarresi, Jason R.; Reichert, Maximilian; Bakir, Basil; Takano, Shigetsugu; Kopp, Janel L.; Wahl‐Feuerstein, Anja; Hicks, Philip; Sander, Maike; Rustgi, Anil K.
Abstract : Background : The plasticity of pancreatic acinar cells to undergo acinar to ductal metaplasia (ADM) has been demonstrated to contribute to the regeneration of the pancreas in response to injury. Sox9 is critical for ductal cell fate and important in the formation of ADM, most likely in concert with a complex hierarchy of, as yet, not fully elucidated transcription factors.Results : By using a mouse model of acute pancreatitis and three dimensional organoid culture of primary pancreatic ductal cells, we herein characterize the Ets‐transcription factor Etv5 as a pivotal regulator of ductal cell identity and ADM that acts upstream of Sox9 and is essential for Sox9 expression in ADM. Loss of Etv5 is associated with increased severity of acute pancreatitis and impaired ADM formation leading to delayed tissue regeneration and recovery in response to injury.Conclusions : Our data provide new insights in the regulation of ADM with implications in our understanding of pancreatic homeostasis, pancreatitis and epithelial plasticity. Developmental Dynamics 247:854–866, 2018 . © 2018 Wiley Periodicals, Inc. Key Findings: Integrin alpha 8 is a novel cell surface marker for a subset of hepatic stellate cells and perivascular mesenchymal cells in developing mouse livers. Integrin alpha 8+ mesenchymal cells maintain the phenotype of hepatoblasts in liver development. In injured liver, myofibroblasts express Integrin alpha 8.